The berenstain bears' seashore treasure eaudiobook - Berenstain, Jan (I Can Read, Level 1: Berenstain Bears., 2012)
The Bear family is all set to have a relaxing time at the shore — but that's before Papa Bear finds a treasure map! Now Papa Bear, Brother Bear, and Sister Bear are all diving into the task of finding the booty. Might it be silver, gold, glittering diamonds, or rubies? In their search, the cubs find many beautiful shells. Could these be the true treasures of the sea? Beginning readers will find this to be a treasure of a tale.